Analisis Faktor-faktor yang Mempengaruhi Kinerja Karyawan Pt. Bank Syariah Mandiri tbk KCP Ma.Bungo - Mustika Mustika (Journal Development, 2016)
This research was conducted to examine the effect of leadership style, individual ability, and performance of employees. This research conducted on all employees (sub-district office district PT.Bank Syariah Mandiri Ma.Bungo) which has 21 people. The method used is a survey method using a questionnaire. Field data subsequently processed using SPSS version 17 kinds of computers, of engineering analysis data used for this research consisted of descriptive statistical analysis which includes determining the average value, median, mode, and standard deviation and inferential statistical analysis which includes the determination of the coefficient of multiple correlation and regression linear.the results of of this research shows that partial and jointly style of leadership, ability of individual and significant influence on employee performance.